Indication of Spatial Justice through the Accessibility of Social Services: Contemporary German Experience - Patoka, I. V.; Krusanov, D. A. (Ukrainian Geographical Journal, 2025)
Ensuring balanced socio-economic spatial development is a crucial foundation for Ukraine’s post-war recovery, particularly for revitalizing war-damaged and depopulated areas, provided that essential security measures are in place. In this context, analyzing the experience of implementing the principles of spatial justice in the territorial organization of living spaces in European countries is crucial. Thus, this paper aims to examine aspects of spatial justice in Germany, focusing on key indicators of access to basic social services. The study highlights that Germany has been transforming its spatial planning standards to ensure equitable living conditions, particularly in terms of access to various services, with a focus on social infrastructure. This paper is the first to identify and analyze spatial development and equity indicators at the district level in Germany, using the example of access to basic social services. A comparative analysis is conducted across districts in different federal states to assess rural area development in terms of spatial justice. The findings demonstrate that peripheral locations and relatively low economic development in some regions of Germany do not necessarily correlate with underdeveloped social infrastructure or limited access to basic social services. This factor promotes greater regional development uniformity and improves spatial justice outcomes, reducing the risk of marginalization in peripheral areas. These insights offer both scientific novelty and practical value for developing recommendations on rural community spatial development in Ukraine, with a focus on spatial justice.